2004
DOI: 10.1021/bi048946z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bacillus thuringiensis (PS149B1) Containing a Cry34Ab1/Cry35Ab1 Binary Toxin Specific for the Western Corn Rootworm Diabrotica virgifera virgifera LeConte Forms Ion Channels in Lipid Membranes

Abstract: The binary Bacillus thuringiensis PS149B1 insecticidal crystal (Cry) protein is comprised of two components, Cry34Ab1, a 14-kDa protein, and Cry35Ab1, a 44-kDa protein, the combination of which forms a novel binary toxin active on western corn rootworm larvae. The permeabilizing behavior of the native binary toxin and its two individual components expressed as recombinant proteins was studied using calcein efflux determination in liposomes and by ion channel activity measurements in planar lipid bilayers (PLBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…As Cry6A, a nematicidal toxin shows low similarity to the three-domain Cry toxins and is lacking any of the five conserved blocks [32,164]. Cry22A and Cry34/Cry35 binary toxin have also been estimated with diverse structural characteristics [14,165,166]. As the number of discovered toxins rises, and novel structures are being solved, a new member of B. thuringiensis toxins would be described under these three categories or even according to other unidentified groups in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As Cry6A, a nematicidal toxin shows low similarity to the three-domain Cry toxins and is lacking any of the five conserved blocks [32,164]. Cry22A and Cry34/Cry35 binary toxin have also been estimated with diverse structural characteristics [14,165,166]. As the number of discovered toxins rises, and novel structures are being solved, a new member of B. thuringiensis toxins would be described under these three categories or even according to other unidentified groups in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not report results in their publication, Ellis et al (2002) indicated that mosquito screening assays of the type used to identify mosquitocidal L. sphaericus and B. thuringiensis strains did not identify a similar level of activity for the B. thuringiensis binary Cry34Ab1/Cry35Ab1 proteins. Moreover, Cry34Ab1 is the protein responsible for the majority of the insecticidal properties of maize 59122, and both proteins are needed to attain full membrane permeabilisation and insecticidal activity (Ellis et al, 2002;Masson et al, 2004). It is unlikely that Cry35Ab1 is active against dipterans, as the conditions in the gut of dipterans and coleopterans differ substantially (acidic in copleopterans and alkalic in dipterans).…”
mentioning
confidence: 99%
“…All of the other Toxin_10 proteins act with their specific partner proteins to form binary toxins as follows: BinA and BinB (both Toxin_10 proteins) (Broadwell et al, 1990;Oei et al, 1990); Cry34 (aegerolysin-like) and Cry35 (Toxin_10) (Kelker et al, 2014;Masson et al, 2004); Cry48 (3-domain) and Cry49 (Jones et al, 2007). The role of each protein in these binary pairs is clearly significant to understanding the specificity of the toxins and potential binding of both components presents further challenges to prediction.…”
Section: Sphaericus B Thuringiensis Bacillus Cereus and Paenibamentioning
confidence: 99%